Engineering ethics : contemporary and enduring debates - Johnson, Deborah G., 1945- (New Haven : Yale University Press, 2020)
An engaging, accessible survey of the ethical issues faced by engineers, designed for students.
8 Is Social Justice in the Scope of Engineers' Social Responsibilities? -- Conclusion -- Notes -- Index.
Description based upon print version of record.
JSTOR
Keywords: Engineering ethics; Ingénieurs -- Déontologie.; Technology & Engineering / Social Aspects; Engineering ethics; Electronic book